PENERAPAN FRAUD RISK MANAGEMENT PADA DIVISI PEMBELIAN PT. LESTARI MENGGUNAKAN ISO 31000:2018 - Yuwono, Matias Andika; Rachmawati, Dyna (Widya Mandala Surabaya Catholic University, 2023)
Research Purposes. This study purpose is to carry out an analysis with the application of good risk management that can provide benefits for companies to reduce the risk of fraud in the company.Research Methods. This research is a qualitative research with a case study with a naturalist approach.Research Results and Findings. The results of the research conducted show that companies that implement risk management well will find it easier to identify the types of fraud risk that can occur in the company. By successfully carrying out the risk identification process, it will make it easier for companies to overcome or deal with fraud risks such as a more effective process of allocating resources, determining strategies to achieve effective internal control, so that by having better preparation it is hoped that the risk of fraud can be minimized in such a way in such a way and does not cause any loss to the company.